Оцінка змін продуктивності і обмежень у форсуванні ходу при збільшенні об’єму доменних печей - Крячко, Г. Ю.; Сігарьов, Є. М. (Physico-technological Institute of Metals and Alloys, 2023)
The selection of the useful volume of new or reconstructed blast furnaces is an urgent task for both manufacturers and designers; therefore, the assessment of the technological capabilities of furnaces of different volumes has always been of interest from both a practical and a theoretical point of view. The purpose of the presented work is the selection of the most representative indicators, with the help of which a comparative assessment of the operation of furnaces of different volumes is possible, the evaluation of the operation of furnaces in the conditions of planned and market economies, as well as an attempt to determine and classify the factors limiting the forced operation of furnaces of increased volume. It is shown that the use of indicators calculated per unit area furnace is not appropriate, since area furnace is not the main size furnace. The main size is full volume furnace, which determines design unit and amount of capital costs for its construction. Specific productivity indicators calculated per unit volume furnace similarly depend on the height furnace and adequately reflect performance of furnaces of different volumes. The indisputable advantage of compact blast furnaces with a useful volume < 1500 m3 in comparison with furnaces of larger volumes is shown, which indicates imperfection of a simplified approach to evaluating performance of furnaces based on the concepts of balance and gas dynamic components, since it is difficult to take into account all the components when determining these components influencing factors. Factors limiting process intensification in blast furnaces of medium and large volumes have been established and classified. The main external factors are the quality characteristics of coke, iron ore materials and blowing, more specifically, hot strength of coke, richness of raw materials in iron and the ability of air blowers to provide blowing with required degree of compression. The main structural solutions to overcome significant limitations in operation of furnaces with a useful volume > 1500 m3 are a rational profile, ratio of output cross-section of air nozzles and cross-section furnace, as well as the use of coneless loading devices.